Hukum Waris Islam: Solusi Akhir Untuk Ketimpangan Sosial Terhadap Perempuan - Miftakur Rohman (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
When a person passes away, most of his rights, according to Islamic law, are given to his heirs and representatives. All property rights, usufructuary rights, and other collateral rights are included in this transferrable right. The Islamic system of inheritance features a broad distribution plan centered on a larger familial circle. The work that must be accomplished for each of the parts determines how they differ from one another. However, there is significant discrimination against the social roles of women. Therefore, a woman's inherited share becomes significant if she is granted the ability to use that portion.